Stiffness and Strength of a Modified External Skeletal Fixator for Orthopaedic Treatment of Animals - Lim, Kok Jeng (2006)
This study outlines the design of a cost effective external skeletal fixator which can be implanted on small animals. A modification for a commercially available Universal Mini External Fixator (UMEXTM) has been done on the biomechanical performance by using a cadaver canine tibia.